Infection patterns and new definitive host records for New Zealand gordiid hairworms (phylum Nematomorpha). (October 2022) - Doherty, Jean-François; Filion, Antoine; Poulin, Robert
Abstract: Some parasites modify the phenotype of their host in order to increase transmission to another host or to an environment suitable for reproduction. This phenomenon, known as host manipulation, is found across many parasite taxa. Freshwater hairworms are known for the behavioural changes they cause in their terrestrial arthropod hosts, increasing their likelihood of entering water to exit the host and reproduce. Understanding how infected arthropods move around in the natural environment could help uncover alterations in spatial distribution or movement induced by hairworms in their terrestrial definitive hosts. Moreover, few hairworm-host records exist for New Zealand, so any additional record could help elucidate their true host specificity. Here, we investigated whether infected terrestrial arthropods were more likely to approach streams in two subalpine communities of invertebrates, using a spatial grid of specialised pitfall traps. Although hairworm infection could not explain the movements of arthropod hosts near streams, we found several new host records for hairworms, including the first records for the recently described Gordionus maori . We also found some new host-parasite associations for mermithid nematodes. These records show that the host specificity of hairworms is quite low, suggesting that their diversity and distribution may be greater than what is currently known for New Zealand. Graphical abstract: Specialised pitfall traps (top left) used in a spatial grid near the stream (right) to detect movement patterns in terrestrial hosts infected with mature hairworms (bottom left). Unlabelled Image Highlights: No patterns in definitive host movement were detected near streams. 11 new hairworm-definitive host records were identified for New Zealand arthropods. First definitive host records for the newly described Gordionus maori are provided. Hairworm prevalence was relatively low across terrestrial host species. New Zealand hairworms can infect a large diversity of terrestrial arthropods.